Praktyki pedagogiczne jako forma rozwijania kompetencji nauczycielskich w opinii studentów - Celińska-Mitał, Dorota (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
Pedagogical training in the education system at a higher level should serve the creation of professionals with a broad theoretical and practical preparation. Pedagogic practice is an integral part of education of every pedagogy student. In view of the ongoing development of student education competencies expected of the modern teacher, we should ask yourself: whether and what have students practical ability to achieve the objectives of the program in their assessment of practices, how in their opinion teaching practice fulfills assumed functions, which, in they consider, of the most important experiences they acquire in the course, how they evaluate the usefulness of ongoing practices in terms of their current or planned professional needs. These are some of the questions that the author was looking for answers in her research.